ANATOMICAL CHANGES OF LIGHT COCONUT WOOD (Cocos nucifera L.) DUE To STEAM-PRESS DENSIFICATION - Krisdianto, Krisdianto (Secretariat of Forestry Research and Development Agency, 2006)
Coconut palm (Cocos nucifera L.) is known as multi-purposes tree as almost all part of the tree can be utilised. Coconut timber utilization is limited on hard or denser part, while lighter coconut timber remains unused. Theoretically, mechanical densification could improve physical properties of light coconut timber, which may be useful for diversifying its uses. This study examined some anatomical changes in coconut wood that occurred during mechanical densification. Coconut wood samples measuring 40 mm thick, 40 mm wide and 50 cm long were steamed at 1260C for 30 minutes prior to being compressed by 23.75 kg/cm2Â Â pressure. Anatomical measures were undertaken using light microscope and scanning electron microscope on both non-compressed and compressed samples. Results showed that the treatment significantly reduced void volume and increased vascular bundles frequency, decreased vessel and parenchyma cell diameter. The wood density also increased by more than 50%.